2023
DOI: 10.3390/brainsci13020171
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance in Short Sleep Young Adults with Different Physical Activity Levels: A Cross-Sectional fNIRS Study

Abstract: Short sleep is a common issue nowadays. The purpose of this study was to investigate prefrontal cortical hemodynamics by evaluating changes in concentrations of oxygenated hemoglobin (HbO) in cognitive tests among short-sleep young adults and to explore the relationship between sleep duration, physical activity level, and cognitive function in this specific population. A total of 46 participants (25 males and 21 females) were included in our study, and among them, the average sleep duration was 358 min/day. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…As a type of motor tissue, skeletal muscle can be effectively improved through appropriate exercise, which is an intervention that contributes to preventing and treating MG. Regular exercise helps to increase muscle strength, [ 63 ] enhance neurological function, [ 64 ] promote better sleep quality, [ 65 ] all of which are important factors in treating MG. Additionally, exercise can help maintain a healthy weight and reduce the risk of other health conditions that may aggravate MG symptoms. However, it is crucial to exercise with caution, and consult with a physician or physical therapist to develop a safe and effective exercise plan tailored to individual needs and limitations.…”
Section: Resultsmentioning
confidence: 99%
“…As a type of motor tissue, skeletal muscle can be effectively improved through appropriate exercise, which is an intervention that contributes to preventing and treating MG. Regular exercise helps to increase muscle strength, [ 63 ] enhance neurological function, [ 64 ] promote better sleep quality, [ 65 ] all of which are important factors in treating MG. Additionally, exercise can help maintain a healthy weight and reduce the risk of other health conditions that may aggravate MG symptoms. However, it is crucial to exercise with caution, and consult with a physician or physical therapist to develop a safe and effective exercise plan tailored to individual needs and limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Lifestyle factors including participating in physical activities have been proved to affect sleep health and muscle quality. A large body of evidence suggested that there were biological and psychosocial mechanisms induced by physical exercise [31][32][33], which may improve sleep symptoms and quality of life. However, in this current study, we found no significant statistical difference in the sufficient recreational activity groups.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Most studies believe PSD or neuropsychiatric condition is closely related to physiological, psychological, social, and lifestyle factors. [22][23][24][25] Previous studies also suggested that PSD is associated with a myriad of factors, such as age, [26] sex differences (greater hazard of developing PSD in females), [27] and education level, [28] but the results appeared to be inconsistent from time to time. Besides, social-psychological factors take part in the occurrence of PSD, such as stressful life events, [29] health education, social support, [30] premorbid neuroticism, [31] insomnia, and the degree of neurological deficit.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%